2020
DOI: 10.3390/metabo10060222
|View full text |Cite
|
Sign up to set email alerts
|

Oxylipin Profiles in Plasma of Patients with Wilson’s Disease

Abstract: Wilson’s disease (WD) is a rare autosomal recessive metabolic disorder resulting from mutations in the copper-transporting, P-type ATPase gene ATP7B gene, but influences of epigenetics, environment, age, and sex-related factors on the WD phenotype complicate diagnosis and clinical manifestations. Oxylipins, derivatives of omega-3, and omega-6 polyunsaturated fatty acids (PUFAs) are signaling mediators that are deeply involved in innate immunity responses; the regulation of inflammatory responses, including acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In patients with neurological symptoms, increased serum levels of lipid peroxidation and reactive oxygen species (ROS) markers, such as malondialdehyde (MDA) and glutamate, along with cytokines (IL6, IL8, IL10, and TNF-α) have been described [ 141 ]. In addition, a profile of polyunsaturated fatty acids named oxylipins was differentially detected in WD patients, which act as mediators in oxidative stress injury and inflammation [ 142 ]. Consequently, these analytes could potentially be used to assess the progression of neurological symptoms.…”
Section: The Need For Biomarkers For a Better Diagnosismentioning
confidence: 99%
“…In patients with neurological symptoms, increased serum levels of lipid peroxidation and reactive oxygen species (ROS) markers, such as malondialdehyde (MDA) and glutamate, along with cytokines (IL6, IL8, IL10, and TNF-α) have been described [ 141 ]. In addition, a profile of polyunsaturated fatty acids named oxylipins was differentially detected in WD patients, which act as mediators in oxidative stress injury and inflammation [ 142 ]. Consequently, these analytes could potentially be used to assess the progression of neurological symptoms.…”
Section: The Need For Biomarkers For a Better Diagnosismentioning
confidence: 99%
“…WD is a rare autosomal recessive disease, caused by mutations in the copper-transporting P-type ATPase-encoding gene ATP7B responsible for the transport of copper into bile from hepatocytes [ 126 ]. Mutations in this gene lead to the accumulation of toxic copper in various tissues and organs, priming for chronic liver disease, CNS abnormalities and psychiatric disturbances.…”
Section: Lipid*omic*s In Rare Diseasesmentioning
confidence: 99%
“…It has been shown that oxylipins are deeply involved in the regulation of inflammatory processes by evoking anti-inflammatory and pro-resolving mechanisms [ 127 ]. Establishing the oxylipin profiles of WD and healthy controls, using the patient’s plasma, revealed an increase in eight oxylipins in WD compared to the controls, indicating an involvement of oxidative stress damage, inflammation and peroxisome proliferator-activated receptor (PPAR) signaling pathways [ 126 ].…”
Section: Lipid*omic*s In Rare Diseasesmentioning
confidence: 99%
“…It was suggested that alterations in Fe metabolism are more pronounced in males than in females and may underlie more severe neuropsychiatric symptoms in male WD patients [268]. Systemic inflammatory response with increased plasma prostaglandins and other oxylipins was found in WD [269]. Additionally, increased serum IL-1 and TNF-alpha was observed in patients with the most severe brain MRI abnormalities [270].…”
Section: Other Genetic Disorders With Brain Iron Depositsmentioning
confidence: 99%